Functional and structural characterization of a novel member of the natriuretic family of peptides from the venom of Pseudocerastes persicus - Amininasab, Mehriar; Elmi, Maryam M.; Endlich, Nicole; Endlich, Karlhans; Parekh, Niranjan; Naderi-Manesh, Hossein; Schaller, Johann; Mostafavi, Hossein; Sattler, Michael; Sarbolouki, Mohammad N.; Muhle-Goll, Claudia (FEBS letters, 2004)
A novel peptide, PNP ( seudocerastes persicus atriuretic eptide), was isolated from the venom of the Iranian viper P. persicus. Amino acid sequencing revealed that the 37-residue peptide belongs to the family of natriuretic peptides. The physiological effects of intra-venously PNP infused into anesthetized rats on urine flow, sodium excretion and blood pressure were comparable to those of atrial natriuretic peptide (ANP). In PC12 cells that were treated with either PNP, ANP, or C-type natriuretic peptide, PNP induced a similar cGMP response as ANP. Since PC12 cells only express the natriuretic peptide receptor (NPR)-A receptor we conclude that PNP binds to the NPR-A receptor. The solution conformation of PNP was characterized using 1H nuclear magnetic resonance spectroscopy and indicates a high degree of conformational flexibility.
Published: 19 December 2003
Gesehen am 28.04.2021